Dividend Taxes and Corporate Behavior: Evidence from the 2003 Dividend Tax Cut - Chetty, R.; Saez, E. (Quarterly Journal of Economics, 2005)
This paper analyzes the effects of dividend taxation on corporate behavior using the large tax cut on individual dividend income enacted in 2003. We document a 20 percent increase in dividend payments by nonfinancial, nonutility publicly traded corporations following the tax cut. An unusually large number of firms initiated or increased regular dividend payments in the year after the reform. As a result, the number of firms paying dividends began to increase in 2003 after a continuous decline for more than two decades. Firms with high levels of nontaxable institutional ownership did not change payout policies, supporting the causality of the tax cut in increasing aggregate dividend payments. The response to the tax cut was strongest in firms with strong principals whose tax incentives changed (those with large taxable institutional owners or independent directors with large share holdings), and in firms where agents had stronger incentives to respond (high share ownership and low options ownership among top executives). Hence, principal-agent issues appear to play an important role in corporate responses to taxation.